Importance of Non-pharmacological Approaches for Treating Irritable Bowel Syndrome: Mechanisms and Clinical Relevance - Orock, Albert; Yuan, Tian; Greenwood-Van Meerveld, Beverley (Frontiers in Pain Research, 2021)
Chronic visceral pain represents a major unmet clinical need with the severity of pain ranging from mild to so severe as to prevent individuals from participating in day-to-day activities and detrimentally affecting their quality of life. Although chronic visceral pain can be multifactorial with many different biological and psychological systems contributing to the onset and severity of symptoms, one of the major triggers for visceral pain is the exposure to emotional and physical stress. Chronic visceral pain that is worsened by stress is a hallmark feature of functional gastrointestinal disorders such as irritable bowel syndrome (IBS). Current pharmacological interventions for patients with chronic visceral pain generally lack efficacy and many are fraught with unwanted side effects. Cognitive behavioral therapy (CBT) has emerged as a psychotherapy that shows efficacy at ameliorating stress-induced chronic visceral pain; however, the molecular mechanisms underlying CBT remain incompletely understood. Preclinical studies in experimental models of stress-induced visceral pain employing environmental enrichment (EE) as an animal model surrogate for CBT are unraveling the mechanism by which environmental signals can lead to long-lasting changes in gene expression and behavior. Evidence suggests that EE signaling interacts with stress and nociceptive signaling. This review will (1) critically evaluate the behavioral and molecular changes that lead to chronic pain in IBS, (2) summarize the pharmacological and non-pharmacological approaches used to treat IBS patients, and (3) provide experimental evidence supporting the potential mechanisms by which CBT ameliorates stress-induced visceral pain.